Continuous synthesis of atomically dispersed Rh supported on MgAl2O4 using two‐stage microreactor. Issue 11 (2nd August 2022) - Xue, Qiangqiang; Yan, Binhang; Wang, Yujun; Luo, Guangsheng
Abstract: Single‐atom catalysts with optimal atom utilization and outstanding activity have penetrated the frontier of heterogeneous catalysis. However, the large‐scale synthesis of this class of catalysts is still a bottleneck for their industrialization. Herein, we suggest a two‐stage micro‐dispersion approach to synthesize mesoporous MgAl2 O4 ‐supported atomically dispersed Rh, which is more competitive than the batch method for boosting the uniform dispersion of Rh. By increasing the Rh loading, single‐atom catalysts (SACs, <0.05 wt%), single‐atom catalysts + nanoparticle catalysts (0.05–0.17 wt%), and nanoparticle catalyst (NPCs, 0.17–1.10 wt%) were obtained. For n ‐octane steam reforming, the turnover frequency of the 0.01‐Rh‐MgAl2 O4 was approximately 30 times that of the 1.10‐Rh‐MgAl2 O4, while the Rh amount of the 0.01‐Rh‐MgAl2 O4 was only 3% that of the 1.10‐Rh‐MgAl2 O4 for the same fuel conversion. Under a high‐temperature (750°C) steam atmosphere for 15 h, the hydrogen formation rate only declined from 25.1 to 23.8 mol/mol‐C8 H18 .